Emphysematous cholecystitis during the treatment of heat stroke. Issue 1 (12th December 2020) - Yoshiyama, Naomasa; Okada, Hideshi; Miyake, Takahito; Kitagawa, Yuichiro; Fukuta, Tetsuya; Yasuda, Ryu; Matsuo, Mikiko; Hatano, Yuichiro; Tomita, Hiroyuki; Yoshida, Shozo; Ogura, Shinji
Abstract : Background: During a heat stroke, microvascular injury may occur as a result of thermal damage and systemic hypoperfusion. We present a case of an older woman who experienced emphysematous cholecystitis during a treatment of heat stroke. Case presentation: A 91‐year‐old woman presented unconscious with a blood pressure, pulse, and core temperature of 73/48 mmHg, 135 bpm, and 39.8°C, respectively. The patient was diagnosed with heat stroke. Twenty‐two hours after arrival, the patient fell into septic shock. We diagnosed emphysematous cholecystitis and performed an emergency cholecystectomy. As the bile culture was positive for Clostridium perfringens, meropenem was administered. The patient was transferred for rehabilitation 32 days after admission. Conclusions: Emphysematous cholecystitis can present during a treatment of heat stroke. An abdominal X‐ray examination should be performed during treatment of heat stroke in the acute phase regardless of the physical assessment. Abstract : We report a case of an elderly woman with no history of diabetes mellitus who experienced emphysematous cholecystitis after the successful treatment of a heat stroke. Emergency cholecystectomy was performed on day 2.